2015
DOI: 10.1371/journal.pone.0123585
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Promotes Neural Stem Cell Proliferation and Differentiation following Hypoxic-Ischemic Injury

Abstract: Neural stem cell (NSC) proliferation and differentiation are required to replace neurons damaged or lost after hypoxic-ischemic events and recover brain function. Periostin (POSTN), a novel matricellular protein, plays pivotal roles in the survival, migration, and regeneration of various cell types, but its function in NSCs of neonatal rodent brain is still unknown. The purpose of this study was to investigate the role of POSTN in NSCs following hypoxia-ischemia (HI). We found that POSTN mRNA levels significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Periostin promotes the proliferation and differentiation of neural stem cells in the brain after ischaemic or haemorrhagic injury 19 , which may rescue neuronal loss and restore brain function 20 . An injection of periostin into the lateral ventricles of hypoxic-ischaemic rats was recently shown to significantly improve spatial learning and memory, indicating that periostin may reverse cognitive deficits after IS 19 . Thus, circulating periostin levels may be associated with post-stroke cognitive impairment rather than the disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periostin promotes the proliferation and differentiation of neural stem cells in the brain after ischaemic or haemorrhagic injury 19 , which may rescue neuronal loss and restore brain function 20 . An injection of periostin into the lateral ventricles of hypoxic-ischaemic rats was recently shown to significantly improve spatial learning and memory, indicating that periostin may reverse cognitive deficits after IS 19 . Thus, circulating periostin levels may be associated with post-stroke cognitive impairment rather than the disability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that the intracerebroventricular administration of recombinant periostin exerts a protective effect after IS 12 , 19 . Based on the consistent changes in periostin levels in the circulation and brain after IS, recombinant periostin may have therapeutic effects when administered via the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…18 Wallace et al's study on autosomal-dominant polycystic kidney disease (ADPKD) presented that periostin was increased in cyst-lining epithelial cells and bound to alphaVbeta3 and alphaVbeta5 integrins, leading to integ-rin-linked kinase activation and cell proliferation compared with normal tubule cells. 19 Besides, other researchers also demonstrated the influence of periostin on cell proliferation in neural stem cells following hypoxia-ischemia, 20 keloid fibroblast, 21 and atrioventricular valve cushions cells. 22 The above data suggested that periostin was a multiple functional regulator on extracellular matrix metabolism and cell proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…POSTN is expressed not only during embryogenesis or pathogenesis [25, 26] (including neoplasia, tissue repair, and cardiac injury) but also in various organs, particularly fibroblast-rich connective tissues such as the skin or breast [27]. POSTN has pivotal functions in heart valvulogenesis [28-30], trabecular meshwork development [31], skin wound healing [32], brain and CNS development [33, 34], and skin aging [35]. However, the role of POSTN in neurocutaneous syndrome has never been described.…”
Section: Discussionmentioning
confidence: 99%